X-Git-Url: http://lambda.jimpryor.net/git/gitweb.cgi?p=lambda.git;a=blobdiff_plain;f=hints%2Fassignment_4_hint_3_alternate_1.mdwn;h=c8bb62c51fafc17b85aa54e62166fb90b6a3ff77;hp=dd55e052ec797db0bb714575a94133c76cf5a304;hb=d437f108ffa48fa141665ffb0b836a9ad53093e7;hpb=1f4f3108441cfd887eb5c9e6ee53a651a80166ea diff --git a/hints/assignment_4_hint_3_alternate_1.mdwn b/hints/assignment_4_hint_3_alternate_1.mdwn index dd55e052..c8bb62c5 100644 --- a/hints/assignment_4_hint_3_alternate_1.mdwn +++ b/hints/assignment_4_hint_3_alternate_1.mdwn @@ -11,13 +11,46 @@ Alternate strategy for Y1, Y2 is implemented using regular, non-mutual recursion, like this (`u` is a variable not occurring free in `A`, `B`, or `C`): - let rec u g x = (let f = u g in A) - in let rec g y = (let f = u g in B) - in let f = u g in C + let rec u g x = (let f = u g in A) in + let rec g y = (let f = u g in B) in + let f = u g in + C or, expanded into the form we've been working with: - let u = Y (\u g x. (\f. A) (u g)) in - let g = Y (\g y. (\f. B) (u g)) in - let f = u g + let u = Y (\u g x. (\f. A) (u g)) in + let g = Y ( \g y. (\f. B) (u g)) in + let f = u g in + C + + We abstract the Y1 and Y2 combinators from this as follows: + + let Yu = \ff. Y (\u g. ff ( u g ) g) in + let Y2 = \ff gg. Y ( \g. gg (Yu ff g ) g) in + let Y1 = \ff gg. (Yu ff) (Y2 ff gg) in + let f = Y1 (\f g. A) (\f g. B) in + let g = Y2 (\f g. A) (\f g. B) in + C + + +* Here's the same strategy extended to three mutually-recursive functions. `f`, `g` and `h`: + + let v = Y (\v g h x. (\f. A) (v g h)) in + let w = Y ( \w h x. (\g. (\f. B) (v g h)) (w h)) in + let h = Y ( \h x. (\g. (\f. C) (v g h)) (w h)) in + let g = w h in + let f = v g h in + D + + Or in Y1of3, Y2of3, Y3of3 form: + + let Yv = \ff. Y (\v g h. ff ( v g h) g h) in + let Yw = \ff gg. Y ( \w h. (\g. gg (Yv ff g h) g h) ( w h)) in + let Y3of3 = \ff gg hh. Y ( \h. (\g. hh (Yv ff g h) g h) (Yw ff gg h)) in + let Y2of3 = \ff gg hh. Yw ff gg (Y3of3 ff gg hh) in + let Y1of3 = \ff gg hh. Yv ff (Y2of3 ff gg hh) (Y3of3 ff gg hh) in + let f = Y1of3 (\f g h. A) (\f g h. B) (\f g h. C) in + let g = Y2of3 (\f g h. A) (\f g h. B) (\f g h. C) in + let h = Y3of3 (\f g h. A) (\f g h. B) (\f g h. C) in + D